Tradisi Timang Turun Mandi pada Masyarakat Kampar: Tinjauan Nilai Budaya dan Nilai Pendidikan Karakter - Alber, Alber; Andriyani, Noni (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
Cultural and educational shifts and changes in Kampar community cause the Timang as the traditional bathing and other traditions are ignored. Kampar society are now more interested in contemporary culture than their ancestors, especially the younger generation. The younger generation is farther away from the tradition adhered to especially when related to degradation and moral decadence which is very different from the youth of the past. Therefore, a deep study of the timang tradition of bathing in Kampar community is needed. The problem in this study related to cultural and character education values in the tradition of the Kampar community, timang bathing. The purposes of this study were to describe, analyze, and interpret the values of cultural ​​and character education in the tradition of taking a bath in the Kampar community. This research was a qualitative research using ethnographic methods. This study has been conducted in six steps, first is the selection of an ethnographic project. Second, asking questions. Third, data collection. Data collection is done by observation, see competent involvement. Fourth, the recording process. Fifth, data analysis. Sixth, the writing process. The data of this study were sourced from the timang tradition of bathing in the community of Kampar Regency. The data examined were documented by being recorded, noted, then analyzed and concluded based on values of cultural and character education contained. The results of this study revealed five cultural values ​​in the timang tradition of bathing in the Kampar community, being obedient, giving advice, loving, loving, and being loyal. Meanwhile, there were three values ​​of character education in the timang tradition of bathing in the Kampar community, such as faith and piety, honesty, and caring.